Physicochemical properties and pasting profiles of composite flour added with cornlettes (Zea Mays) - Abidin, Nurul Ali’im Zainal (Universiti Sains Malaysia, 2015)
Plant - based foods have become human major food source since ages, thus the production of it is crucial. Thus underutilized plant is used to maximizing its usage as well as to accommodate the demands of food production. This study aimed to investigate pasting profiles and morphological characteristics of composite flour containing comlettes powder (CP) which partially replaced wheat flour. Composite flour was prepared using CP mixed with wheat flour (WF) with the proportion of 10:90, 20:80, 30:70 and 100:0 (CP: WF). Composite flour of starch extract was prepared using alkaline isolation method. The results show that amylose content was significantly different (P 0.05) among five samples analysed. Amylose contents significantly increased (P 0.05) when the percentage of comlettes powder in composite flours is increased. The highest amylose content was found in 100% CP sample (4.40g/20g) while the lowest amylose content can be found in control sample (0.072g/20g). The percentage of swelling power in composite flour added with CP was significantly higher than control (p 0.05) and there is significant difference (P < 0.05) in the setback viscosity of the composite flour starch samples. Composite flour shows uniformed wheat starch granules which clustered with irregular shape of comlettes starch granule. In summary, addition of CP to partially replace wheat flour to form composite flour has resulted in improvement of swelling power and amylose composition while slightly altering the starches morphological structures. Thus, composite flour with higher proportions of CP (30:70) can be used to partially replace wheat flour in order to meet the demands of food production.